Distribution and natural history notes on Tachymenis chilensis chilensis (Schlegel, 1837) (Reptilia: Serpentes: Dipsadidae) in Argentina - Giraudo, Alejandro Raul (2012)
We revisit the distribution and natural history data of Tachymenis chilensis chilensis (Schlegel, 1837) in Argentina based on compiled and novel records, extending its northern and southern distribution from the previously known localities in Argentina. We recorded two prey items in Argentinean populations: Rhinella rubropunctata, reported for the first time, and Liolaemus pictus. Tachymenis c. chilensis is mainly found in forested habitats, generally near wetlands with abundant populations of amphibians. The latitudinal range occupied by T. c. chilensis in Argentina is similar to that in Chile, but its northern distribution limit reaches the lowest latitudes in Chile. This is probably due to the higher humidity levels in the western slopes of the Andes and the barrier effect of the highest mountain ranges in this area.